Design of a Monitoring System for Power-consumption Devices Based on Modbus Protocol. Issue 1 (1st December 2022) - Sun, Jinhua; Lin, Jiayuan; Meng, Zhaorui
Abstract: To better monitor the usage status of electric energy for production and living devices, the paper has put forward an electric energy monitoring system based on Modbus protocol, starting by analyzing the demand for monitoring and management of users' electric energy. A three-layer structure has been used in the system, which consists of the sensing layer, control layer, and application layer. The lower computer of the sensing layer used the one-master-multi-slave mode to collect the power data of multiple devices in the bus in real time and transmits the voltage, current, power consumption, and other data of power-consumption devices to the host through the RS-485 interface, Modbus protocol, and GPRS network. Meanwhile, the lower computer interacts with the remote user monitoring terminal to realize the monitoring and management of power consumption data of the devices. The test has shown that the system can steadily monitor and manage the power consumption status of the devices in real time, and can be applied to energy saving, monitoring of power-consumption devices, property management, and other fields, which have good application prospects.